2001
DOI: 10.1063/1.1359776
|View full text |Cite
|
Sign up to set email alerts
|

Thermally poled silica samples are structurally heterogeneous: Electron diffraction evidence of partial crystallization

Abstract: Large structural modifications in v-SiO 2 are found to be induced by ''thermal poling,'' a treatment which makes the glass act as a frequency doubler of an impinging infrared light. The electron diffraction patterns of poled silica plates reveal the presence of a large amount ͑of order 10%͒ of crystallites showing patterns consistent with partial crystallization of the glassy matrix into the cristobalite polymorph of silica.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…This value, close to the breakdown electric field, could induce ionization of the motionless negative charges at the origin of the NL layer, deformation of the Si-O-Si bonds, and partial atomic rearrangement of SiO 2 . [11][12][13] Observations of Si-O-Si angle and Si-O bond length modifications have been reported for example in the literature. 12 Recently, Kashyap has reported that the ͑3͒ susceptibility can be modified by a factor of 2 due to a modification of electronic clouds of bonds under the local electric field.…”
mentioning
confidence: 88%
“…This value, close to the breakdown electric field, could induce ionization of the motionless negative charges at the origin of the NL layer, deformation of the Si-O-Si bonds, and partial atomic rearrangement of SiO 2 . [11][12][13] Observations of Si-O-Si angle and Si-O bond length modifications have been reported for example in the literature. 12 Recently, Kashyap has reported that the ͑3͒ susceptibility can be modified by a factor of 2 due to a modification of electronic clouds of bonds under the local electric field.…”
mentioning
confidence: 88%
“…Although ultraviolet (UV) [8] and thermal [9] poling have been reported to be one of the most efficient way to induce the second-order optical nonlinearity in SiO 2 -related glasses, fibers, and films, the poled glasses show a degradation of the induced nonlinearity even at room temperature, ∼280 days [10]. It has been reported on crystallization with nano-and/or micro-scale particles in these poled glasses [11,12], and become well-understanding of its important role for obtaining large and stable induced second-order optical nonlinearity in the glass.…”
Section: Concept Of Order/disorder Structuresmentioning
confidence: 99%
“…In 2001 Cabrillo et al 59) made an interesting observation of crystallisation in thermally poled silica. TEM images indicated the formation of α-cristobalite.…”
Section: Field Assisted Crystallisationmentioning
confidence: 99%
“…24b) shows they are ~17 nm. Considering Cabrillo's earlier results, 59) it was suggested that these etched voids were evidence of crystallisation: the voids were left when the crystals were preferentially etched away by HF acid. If this interpretation is correct, thermal poling had induced a ~660 nm thick layer, 5.7 μm from the anode, of nanocrystals, with a maximum size of ~20 nm.…”
Section: Field Assisted Crystallisationmentioning
confidence: 99%